2001
DOI: 10.1002/kin.10027
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism associated with the reactions of hydroxyl radicals and of chlorine atoms with 1‐propanol under near‐tropospheric conditions between 273 and 343 K

Abstract: Rate constants for the reactions of OH radicals and Cl atoms with 1-propanol (1-C 3 H 7 OH) have been determined over the temperature range 273-343 K by the use of a relative rate technique. The value of k(Cl + 1-C 3 H 7 OH) = (1.69 ± 0.19) × 10 −12 cm 3 molecule −1 s −1 at 298 K and shows a small increase of 10% between 273 and 342 K. The value of k(OH + 1-C 3 H 7 OH) increases by 14% between 273 and 343 K with a value of (5.50 ± 0.55) × 10 −12 cm 3 molecule −1 s −1 at 298 K, and further when combined with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 34 publications
5
25
0
Order By: Relevance
“…The NO is rapidly decreased after the initiation of the reaction and NO 2 is formed, so the main fate of the acylperoxy radicals will be the formation of corresponding stable acyl peroxynitrate and not lower aldehyde [17,25]. Regarding the increase in product yields of CH 3 CHO and CO, a similar trend for acetaldehyde was reported by Cheema and coworkers [26] when they studied the mechanisms of Cl atom reaction with propanol. In this work, the reason might be that the degradation of alkylperoxy radicals to alkoxy radicals is the key process for both formation of CH 3 CHO and CO.…”
Section: Chsupporting
confidence: 54%
“…The NO is rapidly decreased after the initiation of the reaction and NO 2 is formed, so the main fate of the acylperoxy radicals will be the formation of corresponding stable acyl peroxynitrate and not lower aldehyde [17,25]. Regarding the increase in product yields of CH 3 CHO and CO, a similar trend for acetaldehyde was reported by Cheema and coworkers [26] when they studied the mechanisms of Cl atom reaction with propanol. In this work, the reason might be that the degradation of alkylperoxy radicals to alkoxy radicals is the key process for both formation of CH 3 CHO and CO.…”
Section: Chsupporting
confidence: 54%
“…On the basis of the kinetics and mechanisms of the reaction of Cl atoms with n ‐propane and n ‐butane measured by Tyndall et al 25, average values of 7.6 × 10 −11 and 3.1 × 10 −11 cm 3 molecule −1 s −1 can be derived for the Cl attack at per‐CH 2 and per‐CH 3 group in alkanes. Cheema et al 26 have carried out a quantitative analysis for the reaction of Cl atoms with n ‐propyl alcohol, and they estimated values of 8.7 × 10 −11 , 4.7 × 10 −11 , and 2.2 × 10 −11 cm 3 molecule −1 s −1 for the Cl attack at α‐CH 2 , β‐CH 2 , and γ‐CH 3 group, respectively. The activities of β‐CH 2 and γ‐CH 3 groups in n ‐C 3 H 7 OH towards Cl atom attack are clearly lower compared with the CH 2 and CH 3 groups in alkanes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the rate coefficients for the reactions of n ‐propanol and iso ‐propanol with OH in the gas phase 5–15. Even though the reported values of k 1 (298 K) agree well with each other, the values of k 1 below 298 K are uncertain.…”
Section: Introductionmentioning
confidence: 95%
“…Even though the reported values of k 1 (298 K) agree well with each other, the values of k 1 below 298 K are uncertain. There are two measurements of k 1 below 298 K, one an absolute determination 13 and the other a relative rate study 14; they disagree with each other. There is good agreement among the reported values of k 2 (298 K) 7–13,15.…”
Section: Introductionmentioning
confidence: 99%